Ocorrência de acidentes com material biológico entre profissionais de unidades básicas de saúde - Holanda, Marília Lima de (2014)
Accident at work involving potentially contaminated biological material is a frequent event among professionals belonging to the nursing team, particularly nursing assistants and technicians from health institutions and they constitute on important public health issues. Studies that address this issue in Basic Health Units are scarce. In the present study, we investigated the occurrence of accidents involving exposure to biological material among nursing assistants and technicians at the 16 UBS from the 3rd Regional Executive Secreteriat of the Fortaleza county, the past five years. It is a study of recall field of quantitative, descriptive and exploratory conducted with 97 nursing assistants and technicians. The data collection occurred through a questionnaire the data were analyzed using SPSS version 15.0. The work obeyed the norms of human research and was approved by the Ethics Committee in research of the Federal University of Ceará, opinion number 401 099. One third of participants (29.9%) was a victim of accident at work involving biological material UBS in the past five years, with highlight going to those that were caused by sharp objects (70%). We emphasize more frequent accidents occurring in rooms vaccine (40%), which drilled (75%) ends of the upper limbs with needles (64.3%) previously contaminated with blood (85%) of patients. Among the professionals who have suffered accidents, 70% did not report the accident and did not consider this an important conduit was the main reason. We conclude that, in primary care, accidents with biological material, especially those involving sharp instruments that pose risks to health professionals working in UBS occur. The underreporting is a problem to be solved. We recommend the development of permanent education activities on biosafety with health professionals from the basic health units.